2020
DOI: 10.3390/ijerph17145250
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence, Health, Well-Being, and Work Satisfaction before and after Implementing Activity-Based Workplaces

Abstract: Activity-based workplaces (ABWs) are implemented with possible implications for health, well-being, and work satisfaction in the workplace. Drawing on the theoretical framework, i.e., sense of coherence (SOC), the aim was to investigate how indicators pf SOC—meaningfulness, manageability and comprehensibility—are associated with, or function as barriers or facilitators for, health, well-being and work satisfaction during relocation to an ABW. We followed the implementation of ABWs at the Swedish Transport Admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 31 publications
3
31
3
Order By: Relevance
“…The results showed that, on average, environmental satisfaction decreased in the ABO, which is in line with similar relocation studies (Haapakangas et al , 2018; Ruohomäki et al , 2019). Second, the perceptions of the process before the relocation were associated with a change in environmental satisfaction even a year after the relocation took place, complementing earlier studies, which have shown associations between the implementation process and employee satisfaction (Brunia et al , 2016; Rolfö et al , 2018; Wijk et al , 2020). In this case study, the personnel perceived shortcomings in change management, especially in their opportunities to really influence the decision-making and design process, as well as to receive accurate information.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The results showed that, on average, environmental satisfaction decreased in the ABO, which is in line with similar relocation studies (Haapakangas et al , 2018; Ruohomäki et al , 2019). Second, the perceptions of the process before the relocation were associated with a change in environmental satisfaction even a year after the relocation took place, complementing earlier studies, which have shown associations between the implementation process and employee satisfaction (Brunia et al , 2016; Rolfö et al , 2018; Wijk et al , 2020). In this case study, the personnel perceived shortcomings in change management, especially in their opportunities to really influence the decision-making and design process, as well as to receive accurate information.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, such changes require long follow-up periods, as they involve profound changes in organizational culture and employee behavior. The follow-up periods of most previous relocation studies have been less than one year (Rolfö, 2018; Wijk et al , 2020; Gerdenitsch et al , 2017: Arundell et al , 2018; Blok et al , 2012), with a few exceptions (Bergsten et al , 2021; Haapakangas et al , 2019; Meijer et al , 2009).…”
Section: Management Of Workplace Changesmentioning
confidence: 99%
“…Ruohomäki et al (2015) related sense of coherence to office relocation, but no explicit relation was made to the physical environment. Similarly, a recent case study investigated indicators of sense of coherence during relocation to an activitybased office with a two-wave questionnaire and focus group interviews (Wijk et al, 2020). The study showed that meaningfulness, manageability, and comprehensibility, significantly increased from baseline to nine months post-relocation, given that the implementation process facilitates sense of coherence with support, tools on how to work in an activity-based office, and clear communication.…”
Section: Meaningfulnessmentioning
confidence: 99%
“…Blok et al, 2009;Candido et al, 2019;Gerdenitsch et al, 2018;Rolfö et al, 2018) which may be enough time for employees to adjust to the new environment and capture novelties. According to Wijk et al (2020), a follow-up after nine months may be too short, as they did not find any changes in health after a move to an activity-based office from multiple office types. Short-term evaluations are therefore not sufficient to give in-depth knowledge on how novelties are appropriated over time.…”
Section: Introductionmentioning
confidence: 98%
“…Roskams and Haynes [ 30 ] proposed a conceptual framework that identified environmental demands and resources influencing SOC, such as a clear set of behavioral rules, biophilic design solutions, and design that supports social cohesion, physical activity, and personal identity expression. Similarly, a recent longitudinal case study investigated indicators of SOC during relocation to an activity-based office with a questionnaire and focus group interviews [ 31 ]. The study showed that all SOC indicators were positively associated with overall health, well-being, and work satisfaction.…”
Section: Theoretical Frameworkmentioning
confidence: 99%